2016
DOI: 10.1590/2175-7860201667108
|View full text |Cite
|
Sign up to set email alerts
|

Fabaceae na Floresta Nacional (FLONA) de Assú, semiárido potiguar, nordeste do Brasil

Abstract: ResumoFabaceae é a família mais diversa na flora do Brasil, inclusive na Caatinga, principal região natural do nordeste brasileiro. Este trabalho consiste no estudo taxonômico da família Fabaceae na Floresta Nacional (FLONA) de Assú, município de Assú, estado do Rio Grande do Norte, Brasil. Foram registradas 37 espécies distribuídas em 22 gêneros e 3 subfamílias: Caesalpinioideae (07 spp.), Mimosoideae (11 spp.) e Papilionoideae (19 spp.), das quais: Poincianella bracteosa, Mimosa camporum, Mimosa sensitiva, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
5
0
7
Order By: Relevance
“…Some species were originally absent only in RN state, such as Clidemia hirta (Melastomataceae), while others were unknown in several other northeastern Brazilian states, such as Inga vera (Fabaceae) (also unknown in Alagoas and Sergipe) and Amburana cearensis (Fabaceae), which is categorized as endangered (Americas Regional Workshop 1998). Amburana cearensis was recently recorded for RN (Amorim et al 2016) and currently is only absent in Sergipe. We also improved occurrence data of species with restricted distributions, such as Stilpnopappus laiseae (Asteraceae) and Ayenia erecta (Malvaceae), which were previously reported only from Piauí, and Sorghum bicolor var. arundinaceum (Poaceae), which was previously known only from Acre.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some species were originally absent only in RN state, such as Clidemia hirta (Melastomataceae), while others were unknown in several other northeastern Brazilian states, such as Inga vera (Fabaceae) (also unknown in Alagoas and Sergipe) and Amburana cearensis (Fabaceae), which is categorized as endangered (Americas Regional Workshop 1998). Amburana cearensis was recently recorded for RN (Amorim et al 2016) and currently is only absent in Sergipe. We also improved occurrence data of species with restricted distributions, such as Stilpnopappus laiseae (Asteraceae) and Ayenia erecta (Malvaceae), which were previously reported only from Piauí, and Sorghum bicolor var. arundinaceum (Poaceae), which was previously known only from Acre.…”
Section: Discussionmentioning
confidence: 99%
“…However, the knowledge of RN’s flora is growing rapidly. New species have recently been discovered (Sobral 2010, Araújo and Alves 2013, Lourenço et al 2013, Terra-Araújo et al 2013, Ribeiro et al 2015b, Souza et al 2016) and new occurrences for genera or species have been reported for RN (Versieux et al 2013a, 2013b, São-Matheus et al 2013, Magalhães et al 2014, Amorim et al 2016, Colombo et al 2016, Gomes-Costa and Alves 2016). In five years, the number of species records for RN increased by 78% (BFG 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para a determinação das subfamílias foi utilizada a chave de identificação do Leguminosae Phylogeny Working Group (LPWG 2017). As identificações de gêneros e espécies foram baseadas em literatura especializada (Nobre et al 2008;Lima et al 2009;Queiroz 2009;Setúbal et al 2010;Lima et al 2011;Dourado et al 2013;São-Mateus et al 2013;Cardoso et al 2014;Ferreira et al 2015;Almeida et al 2015;Silva et al 2015;Amorim et al 2016;Snak & Queiroz 2016;Tozzi 2016). Os tipos de hábitos foram definidos com base em observações em campo.…”
Section: Coleta De Dados E Tratamento Taxonômicounclassified
“…The specimens collected and identified by comparison with the material, specialized bibliographies [20,7,21,22,33], books, virtual herbarium and taxonomic keys following the recommended classification methodologies [24,2] and sending samples to specialists in the group for reconfirmation of identification. Proceeding with the species identification, exsiccate assembly, all allocated at Herbarium Prof. Aluízio Bittencourt (HABIT), together, with other Fabaceae family exicts, contained in the herbarium, where all identification and field data stored in exsiccate information sheets, organizing and updating the collection.…”
Section: Survey and Treatment Of Botanical Materialsmentioning
confidence: 99%